Cost, power consumption and performance analysis in SDM ROADM architectures for uncoupled spatial channels - Silva, M. Q. (2022)
Currently optical networks are reaching their maximum transport capacity. Different solutions can be used to overcome this capacity limit, but we are going to study, in particular, space division multiplexing (SDM). To use SDM, the reconfigurable optical add/drop multiplexers (ROADMs) need to be adapted to support this multiplexing. In this paper we analyze four switching strategies used in SDM ROADMs and the respective SDM ROADM architectures. These strategies are explained and analyzed, for uncoupled scenarios, in terms of cost and power consumption. The impact of the physical layer impairments (PLIs) amplified spontaneous emission noise, non-linear interference, passband narrowing due to optical filtering and in-band crosstalk is also assessed, considering a cascade of SDM ROADMs with spatial and spatial-wavelength switching granularities. The PLI inband crosstalk, has insignificant impact, in networks with a single spatial channel or in SDM networks with spatial granularity ROADM architecture, but in a SDM network with spatial wavelength granularity this PLI can lead to an OSNR penalty of around 2 dB, when the number of spatial channels is high. The other PLIs have similar impacts in all networks studied.